Specially designed and CAD/CAM manufactured allogeneic bone blocks using for augmentation of a highly atrophic maxilla show a stable base for an all-on-six treatment concept: a case report - Florian Pfaffeneder-Mantai; Oliver Meller; Benedikt Schneider; Julius Bloch; Ditjon Bytyqi; Walter Sutter; Dritan Turhani (SpringerOpen, 2022)
Abstract Background In terms of a highly atrophic maxilla, bone augmentation still remains very challenging. With the introduction of computer-aided design/computer-aided manufacturing (CAD/CAM) for allogeneic bone blocks, a new method for the treatment of bone deficiencies was created. This case report demonstrates the successful use of two specially designed and CAD/CAM manufactured allogeneic bone blocks for a full arch reconstruction of a highly atrophic maxilla with an all-on-six concept. Case presentation We report the case of a 55-year-old male patient with a highly atrophic maxilla and severe bone volume deficiencies in horizontal and vertical lines. In order to treat the defects, the surgeon decided to use a combination of two allogeneic bone blocks and two sinus floor augmentations. The bone blocks were fabricated from the data of a cone beam computed tomography (CBCT) using CAD/CAM technology. After the insertion of the two bone blocks and a healing period of 7 months, six dental implants were placed in terms of an all-on-six concept. The loading of the implants took place after an additional healing time of 7 months with a screw-retained prosthetic construction and with a milled titanium framework with acrylic veneers. Conclusion The presented procedure shows the importance of the precise design of CAD/CAM manufactured allogeneic bone blocks for the successful treatment of a highly atrophic maxilla. Proper soft-tissue management is one of the key factors to apply this method successfully.